Conceptualizing Recovery from Mental Illness in Indonesia: A Scoping Review - Cohen, Flora; Sugianto, Agus; Pols, Hans; Bayetti, Clement (Makara Human Behavior Studies in Asia, 2024)
Understanding how recovery is defined and realized across different cultural contexts is vital to upholding the dignity and rights of people with mental illnesses. Within the Indonesian context, there is a dearth of research on conceptualizations of recovery from mental illnesses. Questions remain regarding the extent to which service users and providers share common definitions of recovery. We conducted a scoping review to interrogate current definitions of recovery from the perspectives of the various actors working with people with lived experiences of mental illness and extreme mental distress. We found that definitions of recovery differ across multiple domains and include elements of clinical, functional, social, and spiritual recovery. This scoping review contributes to the literature on recovery among individuals with mental illness and psychosocial disabilities while also providing recommendations for improving service delivery.